Self-Efficacy, Well-Being, And Work Engagement of City Marshalls at Binan City, Laguna - Borce, Jomar E.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Leaders are born and then made. However, leaders always look forward to their organization, they seek new experiences and being constant to self-introspection made. The objective of this study was to undermine the level of self-efficacy, well-being, and work engagement, probe the relationship between the respondents’ level of self-efficacy and well-being, the level of self-efficacy and level of work engagement, and the well-being and level of work engagement, and discover the predictive ability of the level of self-efficacy, and well-being, taken singly or in combination, of level of work engagement of City Marshalls at Binan City, Laguna. The findings revealed that there was a multiple correlation between the respondents ‘level of self-efficacy, well-being, and level of work engagement. Further, the ANOVA showed that the independent variable intellectual well -being statistically significantly predicted the dependent variable level of work engagement with an F-value of 33.775 and a probability value of 0.000 which was less than the 0.05 significance level. This implied that the independent variables emotional and intellectual well-being were the drivers of work engagement, which further suggested that the city Marshall’s genuine desire to learn and seek to be challenged in order to improve and grow as an individual determine their commitment to help the organization achieve its goals, which were demonstrated by how they think, feel, and act, as well as the emotional connection they feel towards the organization, work, and team. This study is believed to be a helpful reference for the study’s respondents in carefully and critically exercising their functions and roles with impartiality, neutrality, and non-partisanship, such as mediation and arbitration.